2014
DOI: 10.1038/ncomms5050
|View full text |Cite
|
Sign up to set email alerts
|

Quasi-specific access of the potassium channel inactivation gate

Abstract: Many voltage-gated potassium channels open in response to membrane depolarization and then inactivate within milliseconds. Neurons use these channels to tune their excitability. In Shaker K+ channels, inactivation is caused by the cytoplasmic amino terminus, termed the inactivation gate. Despite having four such gates, inactivation is caused by the movement of a single gate into a position that occludes ion permeation. The pathway that this single inactivation gate takes into its inactivating position remains … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 29 publications
(53 reference statements)
3
16
0
Order By: Relevance
“…Interestingly, we found that the recovery from inactivation kinetics for the new channels, resembled the potassium channels containing less than four identical Shaker channel subunits 54 , 55 , 69 . We have presented evidence that the Shaker channel subunits heterotetramerize with the squid K V channel subunits in Xenopus oocytes (Fig.…”
Section: Discussionmentioning
confidence: 84%
“…Interestingly, we found that the recovery from inactivation kinetics for the new channels, resembled the potassium channels containing less than four identical Shaker channel subunits 54 , 55 , 69 . We have presented evidence that the Shaker channel subunits heterotetramerize with the squid K V channel subunits in Xenopus oocytes (Fig.…”
Section: Discussionmentioning
confidence: 84%
“…However, the electrode resistance of the GDC cell is only slightly lower than that of the SDC-based cell, being 0.056, 0.116 and 0.242 Ω cm 2 at these respective temperatures. Taking into consideration the ease and low-cost of the ceramic fabrication processes involved in the necessary scale-up5, GDC electrolyte fuel cells can be fabricated to a thickness of approximately 10–14 μm, though further reduction in GDC thickness is expected to boost the single cell performance by lowering its ohmic resistance69. Overall, the performance of the SCNT-based fuel cell surpasses the target of 500 mW cm −2 for SOFCs44, suggesting the possibility of practical operation even below 450 °C.…”
Section: Resultsmentioning
confidence: 99%
“…However, the low operating temperature (450-600 °C) typically leads to sluggish kinetics of the oxygen reduction reaction (ORR) at the cathode, with this being a major limitation to LT-SOFC performance456789.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In the Shaker Kv channel, for example, opening of the channel in response to membrane depolarization is only transient because the channel rapidly (msec) enters the N-type inactivated state ( Timpe et al, 1988 ; Zagotta et al, 1990 ). N-type inactivation occurs through a ball-and-chain mechanism wherein the amino-terminal region of the channel plugs the internal pore once it opens in response to membrane depolarization ( Demo and Yellen, 1991 ; Hoshi et al, 1990 ; Venkataraman et al, 2014 ; Zagotta et al, 1990 ; Zhou et al, 2001a2001 ). However, Shaker channels lacking this N-terminal region can still inactivate on a slower timescale (sec) through a process termed slow or C-type inactivation ( Hoshi et al, 1991 ).…”
Section: Introductionmentioning
confidence: 99%